Study of three media one-dimensional photonic crystals with the plane wave expansion (2012)
In this work we present a theoretical study of the optical properties of a three media one-dimensional photonic crystal, designed to have a high efficiency at a wavelength λ, which is chosen arbitrarily. The eigenfrequencies and the eigenstates of the electromagnetic field are obtained through a numerical diagonalization of the Maxwell operator in a plane wave basis. We find that it is possible to make a Bragg reflector obtaining strongly localized states in a cavity of length λ.